2018
DOI: 10.1016/j.scitotenv.2017.11.097
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of PBDEs present in indoor dust: A novel dialysis membrane method with a Tenax TA® absorption sink

Abstract: Human uptake of flame retardants (FRs) such as polybrominated diphenyl ethers (PBDEs) via indoor dust ingestion is commonly considered as 100% bioaccessible, leading to potential risk overestimation. Here, we present a novel in vitro colon-extended physiologically-based extraction test (CE-PBET) with Tenax TA® as an absorptive "sink" capable to enhance PBDE gut bioaccessibility. A cellulose-based dialysis membrane (MW cut-off 3.5kDa) with high pH and temperature tolerance was used to encapsulate Tenax TA®, fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…Similarly to gut bioaccessibility which is partly governed by a pollutant's physico-chemical properties including MW and log Kow 56,57 , inhalation bioaccessibility of PEs decreased against the increasing trend in MW and log Kow (> 4). DiBP pulmonary uptake was 15.5 % and 12 %, in Gamble's solution and ALF, respectively, whereas DnBP and HMW PEs were 10 % and < 5 % bioaccessible in both media, including DEHP and its alternatives, DEHT and DINCH (Fig 1).…”
Section: Inhalation Bioaccessibilitymentioning
confidence: 99%
“…Similarly to gut bioaccessibility which is partly governed by a pollutant's physico-chemical properties including MW and log Kow 56,57 , inhalation bioaccessibility of PEs decreased against the increasing trend in MW and log Kow (> 4). DiBP pulmonary uptake was 15.5 % and 12 %, in Gamble's solution and ALF, respectively, whereas DnBP and HMW PEs were 10 % and < 5 % bioaccessible in both media, including DEHP and its alternatives, DEHT and DINCH (Fig 1).…”
Section: Inhalation Bioaccessibilitymentioning
confidence: 99%
“…K EtOH,w denotes the partition coefficient between dry 100% ethanol and water. 415 For different sorptive sink approaches 9,11,16,17,38,39 , A/V ratios between sink surface area and desorption medium volume (A sink /V solution ) are plotted against their capacity ratio (m sink /m soil ). High A/V ratios provide fast mass transfer of analytes from the desorption solution to the sink, and high capacity ratios are crucial for samples with high K D values.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2.For different sorptive sink approaches9,11,16,17,38,39 , A/V ratios between sink surface area and…”
mentioning
confidence: 99%
“…Furthermore, several in vitro bioaccessibility approaches for dibenz(a,h)anthracene, DBahA; benzo(g,h,i)perylene, BghiP; and indeno(1,2,3-cd)pyrene, IP)(acenaphthene, Ace; fluorene, Fl; phenanthrene, Phe; anthracene, Ant; fluoranthene, Ft; pyrene, Pyr; benzo(a) anthracene, BaA; chrysene, Chry; benzo(e)pyrene, BeP; benzo(b) fluoranthene + benzo(j)fluoranthene, BbF + BjF; benzo(k)fluoranthene, BkF; benzo(a)pyrene, BaP; dibenz(a,h)anthracene, DBahA; benzo(g,h,i)perylene, BghiP; and indeno(1,2,3-cd)pyrene, IP organic compounds involved the use of sorption sinks (i.e. silicone sheet (Gao et al 2019b), Tenax TA® absorption sink (Li et al 2015;Kademoglou et al 2018b) and activated carbon sink (Collins et al 2013)) to capture pollutants as the same time they are released from matrix. The addition of a silicone sheet as sorption skin was observed to increase PAH bioaccessibility ratios up 44 − 67% (Gao et al 2019b).…”
Section: In Vitro Oral Pah Bioavailable Concentrations and Oral Bioavailability Ratios In Pm 10mentioning
confidence: 99%
“…However, in vitro oral bioaccessibility studies of organic pollutants in particulate matter were not found in the literature, while there were some studies applied to indoor/outdoor dust and soils for organic compounds, i.e. PAHs (Tang et al 2006;Kang et al 2011;Collins et al 2013;Li et al 2015;Kademoglou et al 2018a), organophosphate flame retardants (Quintana et al 2017), semi-volatile organic compounds (Raffy et al 2018), polychlorinated biphenyls (Wang et al 2013) and polybrominated diphenyl ethers (Yu et al 2011;Kademoglou et al 2018b;Gao et al 2019b). The stringent analytical requirements (target pollutants enrichment, due to the low levels; and pollutant isolation from the synthetic fluids matrix) for organic pollutant quantification in bioaccessible/bioavailable fractions might explain the scare information.…”
Section: Introductionmentioning
confidence: 99%